Digital Public Relations PT Mulia Industrindo Tbk Dalam Mengelola Akun Instagram @muliaceramics - Fauzi, Nabila Adzhana Putri Ariadi; Hakim, Fadlan Rusman; Saputra, Fadli; Kurniasari, Ni Gusti Ayu Ketut (LPPM Universitas Bina Sarana Informatika, 2024)
Abstract This research aims to analyze the Digital Public Relations (PR) strategy implemented by PT Mulia Industrindo in managing Instagram social media. With the increasing development of technology and social media, companies need to have an effective PR strategy to build and maintain a positive image and interact with audiences directly. This research uses a qualitative method with a case study approach. Data was collected through in-depth interviews with PT Mulia Industrindo's PR team, Instagram content analysis, and documentation. The research results show that PT Mulia Industrindo implements various strategies, such as structured content planning, consistent use of visuals, active interaction with followers, collaboration with influencers, and the use of social media analytics to measure performance. These strategies have proven effective in increasing user engagement, strengthening brand awareness, and supporting a company's marketing goals. This research provides practical insights for other companies looking to optimize their social media management through a strategic Digital PR approach.